Stereotyp(y) muzyki w literaturze - Hejmej, Andrzej (Przestrzenie Teorii, 2007)
The article concerns the question of music in literature, one of the problems of comparative studies, and terms: "non-musicality", "musicality" as stereotypes in literary studies. In the course of considering these views the following problems are discussed: analogy between literature and music (esthetic point of view), "non-musicality" of literature (as quite controversial category in literary research), musical contexts and intertexts (numerous artistic and analytical-literary strategies), contemporary typology of music in literature (S. P. Scher, E. Wiegandt, F. Arroyas, S. Jeanneret).